Gas Turbine Maintenance Optimizing using the Reliability-Centered Maintenance Method - Darmein Darmein; Marzuki Marzuki; Zuhaimi Zuhaimi; Fauzi Fauzi; Nurlaili Nurlaili; Luthfi Luthfi (Jurnal POLIMESIN, 2023)
Gas Turbine is one of the important equipment in the production process in the oil and gas industry. This equipment is used as the prime mover of the compressor to the gas supply. The company has implemented preventive maintenance and condition monitoring in the context of gas turbine maintenance as well as scheduled shutdown every 52,000 hours of operation time. Along with efforts to increase production, the company's management policy has implemented a gas turbine maintenance efficiency program from 52,000 hours to 72,000 hours of operation. This policy is based on the consideration that productivity decreases over time and component replacement during MI (Major Inspection) and HGPI (Hot Gas Path inspection). This policy will certainly have an impact on the reliability, performance, and failure rate that will be experienced by gas turbines as well as their impact on maintenance costs. This study aims to recommend optimal maintenance strategies for gas turbines using the Reliability Centered Maintenance (RCM) method related to availability, reliability, maintainability, and maintenance costs. In this study, an analysis of the causes and effects of failure was carried out using the Failure Mode and Effect Analysis (FMEA) method, with the parameters of failure frequency and consequences of failure then analyzed using the RCM worksheet to determine an effective maintenance strategy.  The results of this study obtained maintenance strategy for Gas Turbine components which are Failure finding, Redesign on conditioning, and Schedule discard task. The components that are scheduled for repairs are compressors and turbines and components that receive a component replacement schedule are Air Inlet and Combustion. The application of the RCM method has been able to reduce maintenance costs by up to 30.678% along with reduced downtime rates, decreased failure rates and the number of MTTR hours